Above‐ and below‐ground biodiversity jointly regulate temperate forest multifunctionality along a local‐scale environmental gradient. (16th March 2020) - Yuan, Zuoqiang; Ali, Arshad; Ruiz‐Benito, Paloma; Jucker, Tommaso; Mori, Akira S.; Wang, Shaopeng; Zhang, Xiaoke; Li, Hui; Hao, Zhanqing; Wang, Xugao; Loreau, Michel
Abstract: Tree diversity has been shown to promote a broad range of ecosystem functions in forests. However, how important these effects are in driving ecosystem multifunctionality in natural forests, relative to other drivers, such as below‐ground biodiversity (e.g. soil microbial diversity), community‐level functional traits and environmental conditions, remains poorly understood. Here, we hypothesize that tree species or phylogenetic diversity (PD), stand structure, functional traits and soil microbial diversity jointly regulate temperate forest multifunctionality (FM) along a local‐scale environmental gradient. Using repeated census data from a 25‐ha old‐growth temperate forest, we first quantified eight ecosystem functions and properties related to above‐ and below‐ground nutrient cycling. We then used these to estimate ecosystem multifunctionality using both averaging and multiple threshold (50%, 75% and 95%) approaches. Finally, we used structural equation models to explore how different facets of tree (tree species, functional and PD) and soil (bacteria, fungi and nematode diversity) biodiversity influence ecosystem multifunctionality, as well as how these relationships are modulated by stand structural attributes and environmental conditions (topography and soil nutrients). Forest multifunctionality was positively related to stand structural complexity but negatively related to acquisitive traits (i.e. community‐weighted mean of specific leaf area). Plant PD had no significant direct effect on FM, but it had a significant indirect effect via increased stand structural complexity. The effect of soil microbial diversity on FM increased with increasing threshold levels of FM and outperformed tree diversity and environmental conditions at the highest threshold level (i.e. 95%). Forests on steep slopes had lower levels of ecosystem multifunctionality due to decreased stand structural complexity. Soil nutrients were responsible for regulating FM via plant trait composition and, to a lesser extent, via tree diversity, stand structure and soil microbial diversity. Synthesis . Plant PD, stand structure and soil microbial diversity jointly regulated FM, and these effects were influenced by local‐scale changes in environmental conditions. Soil microbial diversity was a key driver of highly multifunctional forests, whereas conservation of complex stand structure and conservative trait dominance could enhance mean values of multiple functions. Abstract : Our results suggests that plant phylogenetic diversity, stand structure and soil microbial diversity jointly regulated temperate forest multifunctionality, and these effects were influenced by local‐scale changes in environmental conditions.